Models of Integration of Ukrainian Migrants in Poland in the Context of the Conflict of Historical Narratives: Модели интеграции украинских мигрантов в Польше в условиях конфликта исторических нарративов - Golovashina, Oxana (Przegląd Wschodnioeuropejski, 2019)
The paper studies the integration models used by Ukrainian migrants living in Poland and the resulting problems associated with the rivalry between historical narratives of the Ukrainians and the host community. The author’s work is based on the concept of cultural memory (Maurice Halbwachs, Aleida Assman) and the idea of the dynamic character of images of the past (Jeffrey K. Olik). The data for the study was collected during 30 in-depth interviews with the Ukrainian migrants and also from social networks, forums and open Internet resources. The study has revealed that the majority of the Ukrainian migrants seek to avoid the rivalry between historical narratives, arguing that they personally are not involved in it and events of the past are no longer actual in modern life. Close contacts with representatives of the host community contribute to the assimilation of the Ukrainians. Only a few of the interviewed respondents choose the Ukrainian historical narrative, however they are not going to throw their lot in with Poland. The paper also thoroughly discussed the factors contributing to the choice of one or another position